Czech Student´s Interest in Studying Abroad and Non-European Mobility - Prášilová, Marie; Varvažovská, Pavla; Hubalová, Pavla (International Journal of Membrane Science and Technology, 2023)
The publication is focused on the evaluation of the interest and experiences of students of the Faculty of Economics and Management of students from the Czech University of Life Sciences in Prague (CULS) with international mobility during their studies. The publication evaluates the current development of the number of incoming and outgoing students within the Erasmus+ program and in study programs outside Europe in the years 2008-2019. Based on time series models, the expected development of indicators in the following years were predicted. In the interpretation of the results, factors related to the global epidemiological situation in 2020 and 2021 are taken into account. The solution uses the results of a questionnaire survey carried among outgoing students of the Faculty of Economics and Management. The survey showed that students perceive international mobility as a unique benefit that will make it easier for them to find adequate employment in the labor market in the future. International mobility is highly valued for improving language skills, learning about new cultures and creating foreign social ties.